Factors that Cause the Occurrence of Violent Crimes Against Children - Rika Damayanti; Muhammad Bakri; Nurmisari Nurmisari (Journal La Sociale, 2023)
This research aims to investigate factors that cause the occurrence of violent crimes against children. The data obtained in this research analyzed qualitatively using a descriptive approach (descriptive research) to describe the data obtained, then interpretation and conclusions provided. The results of the research found that Lack of supervision by parents, lack of awareness of children to resolve problems through deliberation, many groups of children are emerging. Meanwhile, efforts made by the police to tackle violent crimes against children in Bone Regency include: Guidance, Peace Efforts, Counseling, Patrols. Providing education to families about the importance of monitoring children so that their children do not become victims of crime or perpetrators of crime. Providing continuous legal education considering the important role of society in preventing crime, especially violent crimes against children.